Psicossomática e tecnologia: stress em jogadores de lan house - Freitas, Cláudia Guimarães Gonçalves (2006)
This dissertation intends to analyze the stress in players from the prolonged use of the network games in LAN HOUSES. It dedicated to trace a revision of the literature about this subject, noticing the bibliographical shortage in relation of the studied object, as well as the references that give support to the concept of Pathological Game. This concept, in general related with the bet among pathological players to define the loss, was enlarged here. The psychosomatic loss transposes the limits that relate it directly with the act of the bet, to detain more specifically in the obstinate and immoderate use of the pleasure object--use that can take Lan House player to suffer himself, in certain measure, the effects of one pathology, such as loss of the time of notion, of the social responsibilities, of their own physiological till financial limits. The objective proposed was to evaluate if the excessive use of the games in Lan Houses can take the player to such losses. For such evaluation, this research adopted the quantitative method by interviewing the visitors of a Lan House, as well as the application of stress tests ESST/VAS and CASIFS/VAS respectively, besides the characterization of the physical space where the network games happen. The evaluation of the results of this study ransomed that the game is before all, a method of socialization by excellence, constituted of the human development and can contain in its unfolded aspects that can promote pathologies resulted from its interaction with the human and the environment it is inserted in